Assessment of soil salinity in Vedaranyam region using remote sensing - S Mohamed Shathir Ali (92313014)
The land use as well as land cover is changing day by day because of human activities. In this study, there are mainly two things are focused such as land use land cover classification of remote sensing images and assessment of soil salinity using remote sensing. Salinity is one of the major problem affecting soil, plants, ground water tables and agricultural lands. According to NRSA / DOS project on $1 (BMapping of salt affected soils of India on 1:250,000 scale$1 (B, the area under salt affected soils in the country is 6.727 million hectares. The study was carried out in Vedaranyam region. Water salinity is usually measured by the TDS (total dissolved solids) or the EC (electric conductivity). TDS is sometimes referred to as the total salinity and is measured or expressed in parts per million (ppm) or in the equivalent units of milligrams per liter (mg/L).There were many methodologies have been discovered to detect soil salinity using Remote sensing and GIS such as NDVI (Normalized Difference Vegetation Index), Soil Adjusted Vegetation Index (SAVI), Salinity Index (SI) and Wetness Index (WI). The main objectives of this study is to check out the capability of remote sensing data and techniques in terms of mapping the land use and land cover classes and detecting soil salinity using different types of salinity indices. The land use land cover classification of the study area has been done using IRS LISS IV and Soil salinity is assessed using Land sat 8 OLI/TIRS. The land use land cover result gives an accurate classification of the study area. Also, the different soil salinity indices revealed a better visualization of saline affected land in the study area. In addition to that there has been made a comparison between supervised classification result, salinity index(SI) and Normalized Difference Salinity Index (NDSI) in order to find out the saline affected lands.s
Keywords: GEOGRAPHICAL INFORMATION SYSTEM; SOIL SALINITY; REMOTE SENSING